In vitro functional effects of XPC gene rare variants from bladder cancer patients. - Qiao, B; Ansari, A; Scott, G; Sak, S; Chambers, P; Elliott, F; Teo, M; Bentley, J; Churchman, M; Hall, J; Taylor, C; Bishop, T; et al. (2011)
The XPC gene is involved in repair of bulky DNA adducts formed by carcinogenic metabolites and oxidative DNA damage, both known bladder cancer risk factors. Single nucleotide polymorphisms (SNPs) in XPC have been associated with increased bladder cancer risk. Recently, rarer genetic variants have been identified but it is difficult to ascertain which are of functional importance. During a mutation screen of XPC in DNA from 33 bladder tumour samples and matched blood samples, we identified five novel variants in the patients' germ line DNA. In a case-control study of 771 bladder cancer cases and 800 controls, c.905T>C (Phe302Ser), c.1177C>T (Arg393Trp), c.*156G>A [3' untranslated region (UTR)] and c.2251-37C>A (in an intronic C>G SNP site) were found to be rare variants, with a combined odds ratio of 3.1 (95% confidence interval 1.0-9.8, P=0.048) for carriage of one variant. The fifth variant was a 2% minor allele frequency SNP not associated with bladder cancer. The two non-synonymous coding variants were predicted to have functional effects using analytical algorithms; a reduced recruitment of GFP-tagged XPC plasmids containing either c.905T>C or c.1177C>T to sites of 408 nm wavelength laser-induced oxidative DNA damage was found in vitro. c.*156G>A appeared to be associated with reduced messenger RNA stability in an in vitro plasmid-based assay. Although the laser microbeam assay is relevant to a range of DNA repair genes, our 3' UTR assay based on Green fluorescent protein(GFP) has widespread applicability and could be used to assess any gene. These assays may be useful in determining which rare variants are functional, prior to large genotyping efforts.